Pengaruh Kualitas Produk, Kualitas Layanan Dan Harga Terhadap Kepuasan Pelanggan Vinila Textile Dan Accessories - Azhari Azhari; Hairudinor Hairudinor; Emy Rahmawati (Universitas Lambung Mangkurat, 2020)
This study aims to examine the effect of Product Quality (X1), Service Quality (X2) and Price (X3) on Customer Satisfaction (Y) on Vinila Textile and Accessories either partially or simultaneously. Samples were taken by 85 customers using accidental sampling technique. Data collection uses a questionnaire while data analysis uses Multiple Linear Regression Analysis through SPSS version 23.The test results prove Product Quality does not have a significant effect on Customer Satisfaction partially, Service Quality has a significant effect on Customer Satisfaction partially, Price has a significant effect on customer Satisfaction partially while simultaneously Product Quality, Service Quality and Price have a significant effect on Customer Satisfaction.Keywords: Product Quality, Service Quality, Price and Customer Satisfaction